2005
DOI: 10.1111/j.1365-2257.2004.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tacrolimus in a patient with pure red-cell aplasia

Abstract: A 78-year-old woman has suffered from pure red-cell aplasia (PRCA) associated with generalized myasthenia gravis and thymoma. Cyclosporin A (CyA) with corticosteroid increased numbers of erythroid cells in her bone marrow cells but she required monthly blood transfusions. Administration of tacrolimus as a substitution for CyA inhibited progression of anemia without the need for further blood transfusion. No serious side effects were observed. This case demonstrates that tacrolimus is another option of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…T-LGL-associated PRCA. Tacrolimus showed activity as a salvage option in a few reports, 37 , 38 and we were able to substantiate those findings in our study. While no head-to-head comparisons were conducted, previous reports suggested lower response rates to CTX vs .…”
Section: Discussionsupporting
confidence: 87%
“…T-LGL-associated PRCA. Tacrolimus showed activity as a salvage option in a few reports, 37 , 38 and we were able to substantiate those findings in our study. While no head-to-head comparisons were conducted, previous reports suggested lower response rates to CTX vs .…”
Section: Discussionsupporting
confidence: 87%
“…Several reports have indicated that in PRCA T lymphocytes play a key role in the production of autoantibodies directed to suppress erythropoiesis (1)(2)(3), and CsA has recently become accepted as the first-line drug for treatment of this disease in Japan (4,5). Tacrolimus can also be used for treatment of PRCA because of the mechanism similar to CsA with selective suppression of the activation of T lymphocytes by acting as a calcineurin inhibitor (6), but our patient was successfully treated with the latter but not with the former. Although the precise reason is unclear, a difference in the intracytoplasmic binding protein between CsA and tacrolimus may be related to these therapeutic outcomes (7).…”
Section: Pure Red Cell Aplasia (Prca) Is An Autoimmune Disorder Charamentioning
confidence: 99%
“…Cyclosporine is reportedly effective in patients with PRCA secondary to thymoma, whereas tacrolimus is not [9]. Although tacrolimus was later reported effective in patients with thymoma-associated PRCA [12], the effectiveness of tacrolimus therapy in patients with PRCA remains unclear. There have been no reports of tacrolimus therapy for anti-EPO PRCA.…”
Section: Introductionmentioning
confidence: 98%